A formação de trabalhadores brasileiros: a experiência do Colégio Isabel - Bevilaqua Marin, Joel Orlando [UNESP] (Univ do Vale do Rio Dos Sinos, 2009)
Colegio Isabel was a project that aimed to "civilize" the indigenous children who lived in the Vale do Araguaia region, Goias Province, to educate national workers and, progressively, incorporate the lands owned by the Indians in the productive process. Colegio Isabel allowed its students a marginal integration in the society, assigning them functions that the so called "civilized" people considered degrading. The egress students lived an ambiguous and marginal life, regarding the original ethnic groups and the adopted society.
The education process of Brazilian workers: Colegio Isabel experience
Keywords: childhood; indigenous matter; indigenous education; professional education